Ballistic Resistance of Steel with the Structure of a Natural Ferrite-Martensitic Composite - V. N. Pustovoit; Yu. V. Dolgachev; Yu. M. Dombrovskii (Безопасность техногенных и природных систем, 2022)
Introduction. For steel armor materials, it is important to reduce the thickness and, consequently, the metal consumption of the protective structure. The previously developed class of materials with the structure of a natural ferrite-martensite composite (NFMC) has characteristics that favor the inhibition of crack development under impact loads and has prospects as an armor material.Problem Statement. The purpose of this work is to evaluate the possibility of using NFMC materials for armor protection devices based on the results of ballistic resistance tests under a high-power concentrated impact (a projectile flying at a hyper-high speed).Theoretical Part. The study of ballistic resistance was carried out on samples of steel 14G2 processed according to various modes. The samples had the shape of plates and a square grid on the surface. Simulation tests of the impact of heat-strengthened dowels from a powder-actuated tool and firing of military small arms at the testing site from an SVD sniper rifle and an AK-74 assault rifle with machine loading ammunition were carried out. The results of simulation tests showed a clear advantage of steel with the NFMC structure. The comparison of the results of firing with military small arms has showed that the ballistic resistance of steel with the NFMC structure depends on the ratio of the volume fractions of ferrite and martensite, which cause different thicknesses of the ductile and strong components of the composite. The highest resistance was observed for a sample with an NFMC structure processed according to the regime: quenching 730°C and tempering 180°C.Conclusions. Steels treated for the NFMC structure can provide effective protection for military personnel with a lower material consumption of armor protection devices, which is due to a special method of braking destruction during a high-power local impact. Thus, the practical application of the developed class of natural composite materials seems promising for obtaining an armor plate with a thinner thickness, which helps to reduce the weight of combat vehicles, increase their mobility and reduce fuel consumption.